Pelatihan Kewirausahaan Terintegrasi, Komprehensif, dan Berwawasan Lingkungan: Menjawab Tantangan Era Revolusi Industri 4.0 - Dewi Sri; Maria. F.S Sulistyawati; Romlah Romlah; Feby Astrid K; Anjelina Puspita Sari (Asosiasi Dosen Akuntansi Indonesia, 2020)
The role of women in improving the family economy is not in doubt. The increasing need demands an increase in the income that the family must earn. With the improvement of technology in the era of the industrial revolution 4.0, it can boost the performance of women who have limited time in promoting their businesses. This entrepreneurship training invites participants to increase promotion in overcoming and participating in business competition. Participants are also invited to be able to use their income to start investing for business development. From the health side, the participants were invited to identify good habits and bad habits. To increase creativity, participants are invited to develop the use of mineral drink bottle caps so that they become marketable products. The method used in this service is by holding a training / workshop where the participants will receive material from the speaker / instructor and be actively involved in activities.